A Survey of Music Therapists Working in Pediatric Medical Settings in the United States. (4th January 2020) - Knott, David; Biard, Marial; Nelson, Kirsten E; Epstein, Stephanie; Robb, Sheri L; Ghetti, Claire M
Abstract: Music therapy is becoming a standard supportive care service in many pediatric hospitals across the United States. However, more detailed information is needed to advance our understanding about current clinical practice and increase availability of pediatric music therapy services. The purpose of this cross-sectional survey study was to collect and summarize data about music therapists working in pediatric medical settings. Specifically, we collected information about (1) therapist demographics, (2) organizational structure, (3) service delivery and clinical practice, and (4) administrative/supervisory responsibilities. Board-certified music therapists working in pediatric medical settings ( n = 118) completed a 37-item online questionnaire. We analyzed survey data using descriptive statistics and content analysis. Findings indicated that there is a ratio of approximately one music therapist for every 100 patient beds, that one-third of respondents are the only music therapist in their setting, and that half of the surveyed positions are philanthropically funded. Prioritizing patient referrals based on acuity was common (95.7%, n = 110), with palliative care and pain as the most highly prioritized needs. More than half of respondents reported serving in high acuity areas such as the pediatric intensive care, hematology/oncology, or neonatal intensive care units. We recommend replication of this survey in five years to examine growth and change in service delivery among pediatric music therapists over time, with additional studies to (a) explore how therapist-to-patient ratios influence quality of care, (b) identify factors that contribute to sustainability of programs, and (c) determine how expansion of services support a broader population of patients and families.